Expression of the Suppressor of Cytokine Signaling-5 (SOCS5) Negatively Regulates IL-4-Dependent STAT6 Activation and Th2 Differentiation - Seki, Yoh-ichi; Hayashi, Katsuhiko; Matsumoto, Akira; Seki, Noriyasu; Tsukada, Jun; Ransom, John; Naka, Tetsuji; Kishimoto, Tadamitsu; Yoshimura, Akihiko; Kubo, Masato (Proceedings of the National Academy of Sciences - PNAS, 2002)
The development of helper T (Th) cell subsets, which secrete distinct cytokines, plays an important role in determining the type of immune response. The IL-4-mediated Janus kinase-signal transducer and activator of transcription signaling pathway is crucial for mediating Th2 cell development. Notably, this pathway is selectively impaired in Th1 cells, although the molecular basis of this impairment remains unclear. We show here that during Th1 differentiation a reduction in the association of Janus kinase 1 with the IL-4 receptor (IL-4R) correlated with the appearance of the suppressor of cytokine signaling-5 (SOCS5). SOCS5 protein was preferentially expressed in committed Th1 cells and interacted with the cytoplasmic region of the IL-4Rα chain irrespective of receptor tyrosine phosphorylation. This unconventional interaction of SOCS5 protein with the IL-4R resulted in the inhibition of IL-4-mediated signal transducer and activator of transcription-6 activation. T cells from transgenic mice constitutively expressing SOCS5 exhibited a significant reduction of IL-4-mediated Th2 development. Therefore, the induced SOCS5 protein in Th1 differentiation environment may play an important role by regulating Th1 and Th2 balance.